Fluorescein-distribution in confocal laser endomicroscopy allows for discrimination between primary brain tumours and metastases - Brielmaier, Maria C.; Reifenrath, Johannes; Ganster, Franziska; Pensel, Nicolas; Gempt, Jens; Meyer, Bernhard; Schlegel, Jürgen; Wagner, Arthur (Frontiers in Surgery, 2025)
IntroductionEmerging digital biopsy technologies, such as confocal laser endomicroscopy (CLE), have shown how neuro-oncological surgery can be revolutionised with the help of rapid, intraoperative tissue assessment which offers a high diagnostic accuracy. For in vivo CLE of cerebral neoplasia, there is only one existing staining agent—Sodium-Fluorescein (SF)—approved for intravenous application. The staining characteristics of SF yet remain unclear.MethodsIn order to understand the dyeing behaviour of SF, we initiated a pilot study, comparing the staining pattern when incubating established tumour cell lines with SF in vitro to the distribution of intravenously applied SF in situ—examined with CLE ex vivo as well in vivo.ResultsIn vitro, the cell lines showed a hyperbolic, time-dependent cellular accumulation of SF. Carcinoma cell lines showed significantly more intracellular SF than glioma cell lines. This phenomenon could be observed when applying SF intravenously before tumour resection surgery. In gliomas and meningiomas, SF could only be detected in 14.3% and 16.1% of images per case, while in carcinoma metastases, SF would accumulate in 68.1% of images per case.DiscussionThe concordant results from in vitro, ex vivo and in vivo investigations could show that the cellular accumulation of the staining agent SF varies depending on the tumour entity. While primary brain tumours rarely show intracellular SF accumulation, carcinoma metastases display SF intracellularly more frequently. Therefore, SF allows for a better discrimination between brain tumours and brain metastases when performing CLE in vivo.